KUAT GESER DINDING BATA RINGAN CELLULAR LIGHTWEIGHT CONCRETE (CLC) DENGAN PENAMBAHAN SERAT FIBER GLASSFIBER REINFORCED CEMENT (GRC) SEBAGAI PENGUAT THIN BED MORTAR - Setiawan, Yanuar; Mulya, Eka Sasmita; Hermawan, Andreas Rudi (Construction and Material Journal, 2025)
One alternative to replacing traditional red brick is lightweight brick, which is commonly used as a wall construction material. One of its main advantages is its light weight, which can help reduce overall construction costs. The reduced weight of the wall material allows for a decrease in the volume of structural elements needed. However, with advancements in material technology, there is a need to further improve the efficiency of lightweight bricks in terms of material usage and the quality of the masonry, particularly its shear strength. This research aims to analyze the optimal fiber placement composition in Cellular Lightweight Concrete (CLC) bricks to enhance the bond strength between bricks compared to that of standard lightweight brick masonry. The test specimens were constructed by assembling wall segments using lightweight bricks measuring 7.5 cm × 20 cm × 60 cm. Compressive strength and horizontal shear strength tests were then conducted on the CLC brick wall assemblies. The results showed that the lightweight bricks had a compressive strength of f'c = 1.07 MPa. The horizontal shear strength without fiber reinforcement was fg = 0.09 MPa, while with fiber reinforcement, it decreased to f'g = 0.06 MPa. Crack patterns were observed at failure displacements of 0.33 mm (non-fiber) and 0.5 mm (with fiber). These findings indicate that the use of GRC fiber in lightweight brick walls resulted in lower horizontal shear strength and displacement performance.